An evaluation of E7 countries' sustainable energy investments: A decision-making approach with spherical fuzzy sets - Rahadian, Dadan; Firli, Anisah; Dinçer, Hasan; Yüksel, Serhat; Hacıo?lu, Ümit; Gherghina, Stefan Cristian; Aksoy, Tamer (Walter de Gruyter GmbH, 2023)
The purpose of this study is to identify important strategies to increase sustainable energy investments in emerging economies. For this situation, first, four different indicators are selected according to the dimensions of the balanced scorecard technique. The weights of these items are computed by using Quantum Spherical fuzzy DEMATEL. In the second phase, emerging seven (E7) countries are ranked regarding the performance of sustainable energy investments. In this process, Quantum Spherical fuzzy TOPSIS is taken into consideration. The main contribution of this study is that prior factors can be defined for emerging economies to increase sustainable energy investments in a more effective way. Furthermore, a novel decision-making model is developed while integrating TOPSIS and DEMATEL with Quantum theory, Spherical fuzzy sets, facial expressions of the experts, and collaborative filtering. It is concluded that competition is the most significant factor for the performance of sustainable energy investments. In addition, the ranking results denote that China and Russia are the most successful emerging economies with respect to sustainable energy investments. It is strongly recommended that emerging countries should mainly consider benchmarking the capacity of energy hubs with the aim of increasing the capacity of ongoing energy plants.
Keywords: DEMATEL; Neuro Decision-Making; Quantum Spherical Fuzzy Sets; Recommender Systems; TOPSIS